ANALISIS PENGELOLAAN BARANG MILIK DAERAH MENURUT PERATURAN PEMERINTAH NOMOR 27 TAHUN 2014 PADA PEMERINTAH KABUPATEN MINAHASA SELATAN - Rorimpandey, Ariel; Nangoi, Grace B.; Manossoh, Hendrik (Universitas Sam Ratulangi, 2016)
Local assets has important role and function for South Minahasa Regency Government to support the wheels of government and public service. The purpose of this study was to analize the suitability of local assets management in South Minahasa Regency Government to Government Regulation No. 27 Year 2014.Â This study was conducted at The Local Agency Of Finance, Revenue And Assets Management In South Minahasa Regency. Local assets management based on Government Regulation No. 27 Year 2014 include requirements planning and budgeting, procurement, use, utilization, security and maintenance, assessment, transfer, destruction, disposal, administration, and guidance, supervision and control. This study is a qualitative descriptive research. The informant was determined by using purposive sampling method. Data analysis was performed with data reduction, data display and conclusion. The results showed basically, the local assets management has been cultivated implemented based on PP No. 27 year 2014, although there are obstacles in implementing local assets management such as the lack of regulation in regency such as local asset management regulation under PP No. 27 year 2014, lack of knowledge and understanding of human resources and lack of leadership commitment of SKPD in local asset management. Keywords : Local assets management, government regulation, local assets